Theatre Histories an introduction - Nellhaus, Tobin; Lei, Daphne Pi-Wei; Underiner, Tamara L. 1958-; Ybarra, Patricia A. 1972- (Routledge, Taylor & Francis Group, 2024)
"This updated 4th edition of Theatre Histories offers a critical overview of global theatre, drama, and performance, spanning a broad wealth of world cultures and periods, integrating them chronologically or thematically, and showing how they have often interacted. Bringing together a group of scholars from a diverse range of backgrounds and approaches to the history of global theater, this introduction to theatre history places theatre into its larger historical contexts and attends to communication's role in shaping theatre. Its case studies provide deeper knowledge of selected topics in theater and drama, and its "Thinking Through Theatre Histories" boxes discuss important concepts and approaches used in the book. Features of the fully updated fourth edition include: · Deeper coverage of East Asian and Latin American theater · Richer treatment of popular culture · More illustrations, photographs, and information about online resources · New case studies, include several written by authoritative scholars on the topic · Pronunciation guidance, both in the text and as audio files online · Timelines · An introduction on historiography · A website with additional case studies, a glossary, recordings of the pronunciation of important non-English terms, and instructor resources · A case studies library listing, including both those in print and online, for greater instructor choice and flexibility This is an essential textbook for undergraduate courses in theatre history, world theatre and introduction to theatre, and anyone looking for a full and diverse account of the emergence, development and continuing relevance of theatre to cultures and societies across the world"--
Keywords: Geschichte; Theater; Theater-History; Theater / History; Performing arts / History